(untitled) (Journal of Human Sciences, 2022)
The problem of the origin of language is among the most important issues in which the philosophy of language is concerned. Almost no philosophy is devoid of discussion and research. In this context, the history of philosophy witnessed a struggle and conflict between two theories of the origin of language. The first argued that it is Tawqifiya. This means it is from Allah, and Allah is beyond it. On the other hand, the second argued that it is a natural product of the phenomenon of human society that occurs between people by complicity and agreement. In the Greek cultural context, the two theories clashed; where the conflict between them was an extension of a deeper philosophical conflict that was the sides of the Soviet School. This school illustrates that the origin of the language was compatibility and convention. This was consistent with the general framework of their philosophy in the time of their opponents. Their opponents from the Peripatetic - Plato and Aristotle - went to the view of the Tawqifiya theory, and the same is true of the Islamic philosophy, which also witnessed the same struggle. Where some philosophers tended to say the Tawqifiya suspensive theory, philosophers have adopted the terminological theory because of its success in explaining a large number of phenomena related to language that the Tawqifiya endowment theory is unable to solve. This is under the influence of some verses of the Noble Qur’an, from which it was understood that the language has a waqf nature. On the other hand, some philosophers, such as the Mu’tazila and Al-Farabi, argued with the terminological theory for its ability to dismantle and overcome some of the problems associated with language at times, and with doctrine at other times. As for contemporary philosophy, many philosophers have adopted the terminological theory because of its success in explaining a large number of language-related phenomena that the Tawqifiya endowment theory is unable to solve. To illustrate all of this, we will use the critical analytical approach when approaching this problem, due to its ability to explain the dimensions of this issue.